Antioxidant Activity And Bioactive Compounds Of Selected Tropical Plants - Mustafa, Roheeyati Ashikin (2009)
Antioxidant does not only prevent food containing lipid and oils from becoming rancid, but it also provides protection against harmful free radical and has been strongly associated with reduced risk of chronic diseases such as cardiovascular diseases, cancer and diabetes. The antioxidant activity of 21 selected tropical plant extracts was evaluated utilizing four different assays including conjugated diene, scavenging DPPH radical, TBA and chelating effect on ferrous ion. Bioactive compounds (total phenolics, flavonoids, β-carotene, lycopene, α-tocopherol and ascorbic acid) were also determined in the plants extracts. Results of the study showed that C.caudatus extract was highly effective in the prevention of conjugated diene formation and scavenging effect on DPPH radicals. On the other hand, C.asiatica and P.tetragonolobus extracts demonstrated excellent activity in inhibiting malondialdehyde (MDA) formation and chelating ability on ferrous ion. As expected, increasing the concentration of extracts used increased the antioxidant activity in all plants tested. The antioxidant activities of some of these plants were found to be as good as that of α- tocopherol and BHA (Butylated hydroxyanisole). Results of the study revealed that L.inermis extracts consisted of the highest content of phenols and then flavonoids (catechin, epicatechin and naringenin) compared to all the plants tested. On the other hand, excellent concentration of quercetin and ascorbic acid were identified in V.negundo extract whilst surprisingly, P.bleo extract showed high content of lycopene and α-tocopherol. Highest kaempferol and myricetin was found in S.grandiflora and C.asiatica extracts whilst luteolin and apigenin were predominantly found in P.cordifolia and K.galanga extracts. On the other hand, highest β-carotene content was found in G.procumbens extract. Excellent correlation (R2=0.8613) was found between radical scavenging activity and the total content of phenolic compounds. Similar correlation (R2=0.8430) was seen between radical scavenging activity and flavonoids compounds. The study suggested that phenolic compounds in particular, the flavonoids contribute to the antioxidant activity. Keywords: Antioxidant activity; tropical plants; bioactive compounds; phenolic compounds; ascorbic acid.